53rd AIAA/ASME/ASCE/AHS/ASC Structures, Structural Dynamics and Materials Conference<BR&amp;gt;20th AIAA/ASME/AHS Adapti 2012
DOI: 10.2514/6.2012-1680
|View full text |Cite
|
Sign up to set email alerts
|

Geometric Programming for Aircraft Design Optimization

Abstract: We propose formulating preliminary-stage aircraft design problems as geometric programs (GPs), which are a specific type of convex optimization problem. Recent advances in convex optimization offer significant advantages over the general nonlinear optimization methods typically used in MDO. Modern GP solvers are extremely fast even on large problems, require no initial guesses or tuning of solver parameters, and guarantee globally optimal solutions. These benefits come at a price: all objective functions and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
47
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(47 citation statements)
references
References 12 publications
0
47
0
Order By: Relevance
“…The corresponding bypass ratio is therefore relatively low. If we raise the turbine inlet temperature, the core airflow can be smaller, thus increasing bypass ratio [2].…”
Section: The Matmentioning
confidence: 99%
“…The corresponding bypass ratio is therefore relatively low. If we raise the turbine inlet temperature, the core airflow can be smaller, thus increasing bypass ratio [2].…”
Section: The Matmentioning
confidence: 99%
“…In this example, we identified a posynomial model for the drag force of the airfoil, from data obtained from the CFD simulations. The posynomial form is important since it allows the application of geometric programming algorithms, which in turn allow for efficient optimization of the airfoil characteristics, see, e.g., [14].…”
Section: Example 2: Identification Of Airfoil Drag Forcementioning
confidence: 99%
“…Note that, while in polynomial models the exponents α ij are nonnegative integers, in posynomial models these exponents may also be negative and/or noninteger. Posynomial models are of great importance in many fields of technology, ranging from structural design, network flow, optimal control (see [2,33]), to aerospace system design [14], circuit design [5,8,26], antennas [1] and communication systems [7]. The interest in posynomials is motivated by the fact that they lead to computationally efficient geometric programming models for optimal system design, see, e.g., [10,2,33].…”
Section: Introductionmentioning
confidence: 99%
“…For problems that can be formulated as Geometric Programs (GPs), modern solvers guarantee globally optimal solutions, are extremely fast, and return local sensitivities at no extra cost, thanks to the principle of lagrange duality. In previous work, Hoburg [1] shows, firstly, that many models common to aircraft design can be represented directly in GP-compatible form, and, secondly, that there are a number of innovative ways of dealing with models that cannot, including, but not limited to, changes of variables and GP-compatible fitting methods. Finally, it is also shown that such problems can be solved efficiently using a standard laptop computer.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, it is also shown that such problems can be solved efficiently using a standard laptop computer. The aircraft design problem solved in [1] includes models for steady level flight, range, takeoff distance, landing speed, sprint flight condition, actuator disk propulsive efficiency, simple drag and weight buildups, and beam wing box structure.…”
Section: Introductionmentioning
confidence: 99%